Potential transfer of aquatic organisms via ballast water with a particular focus on harmful and non-indigenous species: A survey from Adriatic ports. (October 2019) - Cabrini, M.; Cerino, F.; de Olazabal, A.; Di Poi, E.; Fabbro, C.; Fornasaro, D.; Goruppi, A.; Flander-Putrle, V.; Francé, J.; Gollasch, S.; Hure, M.; Lipej, L.; et al.
Abstract: Ballast water discharges may cause negative impacts to aquatic ecosystems, human health and economic activities by the introduction of potentially harmful species. Fifty untreated ballast water tanks, ten in each port, were sampled in four Adriatic Italian ports and one Slovenian port. Salinity, temperature and fluorescence were measured on board. Faecal indicator bacteria (FIB), phyto- and zooplankton were qualitatively and quantitatively determined to identify the species assemblage arriving in ballast water. FIB exceeded the convention standard limits in 12% of the sampled tanks. Vibrio cholerae was not detected. The number of viable organisms in the size groups (minimum dimension) <50 and ≥10 μm and ≥50 μm resulted above the abundances required from the Ballast Water Management Convention in 55 and 86% of the samples, respectively. This is not surprising as unmanaged ballast waters were sampled. Some potentially toxic and non-indigenous species were observed in both phyto- and zooplankton assemblages. Highlights: Ballast water sampling was carried out on 50 ships in five Adriatic ports. Vibrio cholerae was not detected. Viable organisms were detected in >90% of ballast tanks. Six potentially harmful and one non-indigenous phytoplankton species were identified. Six non-indigenous zooplankton species were observed.